Influence of Residency Training on Research Productivity and Plastic Surgery Career. Issue 6 (December 2020) - Roy, Eva; Egro, Francesco M.; Zalewski, Adrian; Smith, Brandon T.; Losee, Joseph E.; Nguyen, Vu T.
Abstract : Background: The impact of residency training on academic productivity and a career in academic plastic surgery remains uncertain. Previous literature has explored the influence of training institutions on academic careers in surgery. The aims of the study were to assess research productivity during plastic surgery residency training and to illustrate how differences in training programs impact resident research productivity. Methods: Academic plastic surgery faculty that graduated in the past 10 years were identified through an Internet search of all Accreditation Council for Graduate Medical Education–accredited residency and fellowship training programs. Research productivity was compared based on h -index, number, and quality of peer-reviewed articles published during residency. Results: Three hundred seventy-five academic plastic surgeons were identified and produced 2487 publications during residency. The 10 most productive training institutions were Johns Hopkins, Georgetown, University of Michigan, Stanford, University of California Los Angeles, Northwestern, Harvard, New York University, University of Pennsylvania, and Baylor. Academic productivity was higher among integrated residents (integrated = 8.68 publications, independent = 5.49 publications, P < 0.0001). The number of publications positively correlated to faculty size ( r = 0.167, P = 0.0013), National Institute of Health (NIH) funding ( r = 0.249, P < 0.0001), residency graduation year ( r = 0.211, P < 0.0001), and negatively correlated with Doximity ranking ( r = −0.294, P < 0.0001). H -index was positively correlated with number of publications ( r = 0.622, P < 0.0001), faculty size ( r = 0.295, P < 0.0001), and NIH funding ( r = 0.256, P < 0.0001) and negatively correlated with Doximity ranking ( r = −0.405, P < 0.0001) and residency graduation year ( r = −0.163, P < 0.0001). Conclusions: Our study has found that there is an elite cohort of programs that are the most productive research institutions. Resident research productivity is higher among integrated residents, recent graduates, and programs that are larger in size, with a higher Doximity ranking and NIH funding. This study can guide medical students and future applicants who are interested in a career in academic plastic surgery in the selection of programs that match their career aspirations.